Did Protestantism Promote Economic Prosperity via Higher Human Capital? - Jeremy Edwards (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper investigates the Becker-Woessmann (2009) argument that Protestants were more prosperous in nineteenth-century Prussia because they were more literate, a version of the Weber thesis, and shows that it cannot be sustained. The econometric analysis on which Becker and Woessman based their argument is fundamentally flawed, because their instrumental variable does not satisfy the exclusion restriction. When an appropriate instrumental-variable specification is used, the evidence from nineteenth-century Prussia rejects the human-capital version of the Weber thesis put forward by Becker and Woessmann.
Keywords: Z12; C26; I20; N33; 330; Protestantism; Weber thesis; human capital; instrumental variables